User rating on the eligibility of the KIPAS model counseling steps - Andi Mappiare-AT; Lutfi Fauzan; Hasti Hastiani (Konselor, 2020)
This research examines the Konseling Intensif dan Progresif yang Adaptif terhadap Struktur counseling model (KIPAS) based on Indonesia's archipelago. In English, this means Intensive and Progressive Counseling Adaptive to Structure. The model constitutes good news (Kabar gembira), data integration and Internalization (Integrasi dan internalisasi data), action planning (Perencanaan tindakan), plan actualization (Aktualisasi rencana), and celebration or certification (Selebrasi/Sertifikasi). Together, these steps form an acronym of KIPAS, a counseling model whose steps should be tested empirically to describe the users’ expectations or ratings. Data were collected using a satisfaction scale and analyzed in a descriptive percentage. The results show that the KIPAS steps are applicable, with user ratings ranging from very feasible to quite feasible.